(3+z)(5z-8)=0

Simple and best practice solution for (3+z)(5z-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3+z)(5z-8)=0 equation:



(3+z)(5z-8)=0
We add all the numbers together, and all the variables
(z+3)(5z-8)=0
We multiply parentheses ..
(+5z^2-8z+15z-24)=0
We get rid of parentheses
5z^2-8z+15z-24=0
We add all the numbers together, and all the variables
5z^2+7z-24=0
a = 5; b = 7; c = -24;
Δ = b2-4ac
Δ = 72-4·5·(-24)
Δ = 529
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$z_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$z_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{529}=23$
$z_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-23}{2*5}=\frac{-30}{10} =-3 $
$z_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+23}{2*5}=\frac{16}{10} =1+3/5 $

See similar equations:

| 9x+3=92x-5 | | 5x+33=16x | | x+7x2-3=37 | | 2=2p-3p | | 12c-3=45 | | 0.5=|x| | | 2(3x-2)-2(2x+7)=30 | | 1=5x-4-2x | | x+7*2-3=37 | | 11+2.5y+5y=-4 | | 4x−10=54 | | 8x-2-4=28 | | 3c-41=c-1 | | 2(3x-2)-4(x-3)=6 | | 3n^2+n-400=0 | | 2w=60 | | 3c–41=c-1 | | x*2-10x-1000=0 | | –4h=–8−5h | | (5y-29)+(3y+19)=180 | | 2x.x=100 | | 5(2x+3x)=96 | | -4(1-5y)=30 | | x-4/5=25/20 | | 4b+35=16b-13 | | 15•9-5=7x+27 | | 25+2t=5(t+|2) | | 30=4u+8 | | -2x-5=-14 | | x-2/3=17/12 | | 9x−8−11x=2+5x+4 | | 3x-12=6x-6* |

Equations solver categories